Perspectives on robust resource allocation for heterogeneous parallel and distributed systems - Maciejewski, Anthony A., author; Siegel, Howard Jay, author; Ali, Shoukat, author; Chapman & Hall/CRC Press, publisher (Colorado State University. Libraries, 2008)
Parallel and distributed systems may operate in an environment that undergoes unpredictable changes causing certain system performance features to degrade. Such systems need robustness to guarantee limited degradation despite some fluctuations in the behavior of its component parts or environment. This research investigates the robustness of an allocation of resources to tasks in parallel and distributed systems. The main contributions of this chapter are (1) a mathematical description of a metric for the robustness of a resource allocation with respect to desired system performance features against multiple perturbations in multiple system and environmental conditions, (2) a procedure for deriving a robustness metric for an arbitrary system, (3) derivation of robustness metrics for three example distributed systems, and (4) design of static heuristics to determine a robust resource allocation for one of the example systems.
Keywords: resource allocation; robustness metric; robustness; resource management systems; parallel and distributed systems